A situational analysis of iron education in New Zealand intermediate and secondary schools : a thesis presents in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Keightley, Jerushah (Massey University, 2022)
Background: Iron deficiency is one of the most common nutritional deficiencies worldwide and is the leading cause of anaemia. Iron deficiency is disproportionately represented in the female population partially due to the significant blood loss experienced during menstruation. Increases in iron education may serve as a preventative method for reducing iron deficiency incidence in females in the general population and may aid in early diagnosis and treatment. Objective: This study aimed to investigate the current level of iron education provided to 11-14-year-old females in New Zealand intermediate and secondary schools by Health, Physical Education (PE), and Nutrition teachers. The secondary objective was to investigate whether these teachers had access to iron education resources. Methods: An anonymous online questionnaire was distributed to nutrition, physical education, and health teachers throughout New Zealand to gain their perspective on what iron (dietary and menstruation) education is provided within their schools. Results: The results reflect a low level of iron education currently being provided, with 52% (26/50) of participants reporting that iron education was not part of their current curriculum. The delivery of iron education was affected by the subject the participant primarily taught (χ²=12.641, p=0.002). Health and physical education teachers were 5.07 times more likely to report they did not teach any iron-specific education compared to nutrition teachers. The primary reasons for not including iron education were lack of time (36%, 9/26) and iron education being too specific (28%, 7/26). Furthermore, the results of this study show only 28% (14/50) of the participants reported having access to iron-related resources. Conclusions: Our findings indicate that there is limited iron education provided to 11-14- year-old female students in New Zealand intermediate and secondary schools. This low amount of iron education is due to a lack of time available for teachers to cover the specific topic in the health and nutrition curriculums. There is potential for an improvement in the provision of educational resources for the delivery of iron education in New Zealand intermediate and secondary schools to aid a more consistent and broad reach of education to students nationwide.
Keywords: 321005 Public health nutrition